Globalization and its impact on human rights - Chunakara, Mathews George; CSS (Organization); Christian Conference of Asia (Tiruvalla : : Christava Sahitya Samithy, 2000)
Contributed articles
"Christian Conference of Asia, Hong Kong."
Keywords: Human rights -- Congresses